Small group intervention linking word study to reading and writing - Dorn, Linda J.; Soffos, Carla; Stenhouse Publishers (Portland : Stenhouse Publishers, 2009)
The ultimate test of a student's knowledge about words is the ability to transfer this information to reading and writing. A word study intervention must include opportunities for students to apply word-solving strategies to connected texts. In this DVD the teacher, Alisa Paladino, works with a small group of fourth-grade students in a word study intervention that links to reading and writing
Title from container
CD-ROM contains facilitator's guide and PowerPoint presentation
DVD format
Keywords: Vocabulary -- Study and teaching (Elementary); Reading (Elementary); English language -- Composition and exercises -- Study and teaching (Elementary)